DNA-demethylation by DAC induces MAGE expression and MAGE-specific T cell reactivity against tumors but also healthy cell subsets - Marije A.J. de Rooij; Miranda H. Meeuwsen; Anne K. Wouters; Dennis F.G. Remst; Renate S. Hagedoorn; Dirk M. van der Steen; Els M.E. Verdegaal; Tassilo L.A. Wachsmann; J.H. Frederik Falkenburg; Mirjam H.M. Heemskerk (Molecular Therapy: Oncology)
Cancer testis antigens (CTAs) can be expressed in tumors, whereas expression is silenced in normal tissue except for the immune-privileged testis. This quasi-tumor-restricted expression makes CTAs attractive targets for T cell receptor (TCR) gene therapy. However, CTA-specific TCR gene therapy is only applicable for tumors with substantial and homogeneous CTA expression. To increase the number of patients eligible for CTA-specific TCR gene therapy, CTA expression can be upregulated with DNA-demethylating agents like 5-aza-2′-deoxycytidine (DAC). Here, we studied the effect of DAC on the recognition of a wide range of tumor cells by TCR-engineered T cells specific for the CTAs MAGE-A1, MAGE-A3/A6, or MAGE-A9. DAC treatment strongly increased MAGE expression in most tumor cell lines tested and strongly induced or improved recognition by MAGE-specific TCR-engineered T cells. However, MAGE upregulation was not limited to tumor cells but also occurred in healthy cells, resulting in MAGE-specific T cell reactivity against proliferating T and B cells. Overall, these results underscore the potential of DAC treatment to induce MAGE expression in tumor cells and to increase their sensitivity for MAGE-specific T cell therapy. However, DAC treatment can potentially result in on-target off-tumor reactivity, warranting careful consideration when using DAC as sensitizing strategy prior to adoptive transfer of CTA-specific T cells.